An overview on effects of micronutrients and macronutrients interventions in management of polycystic ovary syndrome. (December 2022) - Saei Ghare Naz, Marzieh; Jahanfar, Shayesteh; Ramezani Tehrani, Fahimeh
Summary: Polycystic ovary syndrome (PCOS) is one of the common endocrinopathies among women. Changing dietary behaviors for PCOS management has been an important research focus during the last decades. This review has discussed current evidence and clinical trial studies relating to the impact of macronutrients and micronutrients in the management of different clinical feature of PCOS. The possible relationship between the quality and quantity of micronutrients and macronutrients and PCOS as well as the necessity to manage PCOS as a complex condition highlights the importance of diet-related interventions. The growing number of clinical trials related to the effect of micronutrients (zinc, chromium, selenium, vitamin D, inositol, and vitamin E) and macronutrients interventions (manipulation of fat, carbohydrate, protein, and MedDiet, Calorie restriction, Low Glycemic Diet) have been demonstrated to be practical approaches for managing clinical and biochemical features of PCOS, however the potential benefit of micronutrient and macronutrient approaches could be different from one by one, particularly in different phenotypes of PCOS. To achieve optimum outcomes, providing information regarding safety and the best dose selection of micronutrients and macronutrients is necessary. Hence, to better understand the approaches' risk/benefit in women with PCOS, future trials with a large sample size are recommended.